Between machines and art: The impact of CNC technology on artistic creation - Marcelo Fraile-Narváez; Mihaela I. Chidean (Array, 2025)
This study shows how a hybrid workflow based on a Style-GAN-3 (with 256 × 256 pixel resolution) together with a €185 open-hardware plotter reframes authorship by uniting algorithmic invention with material execution. Specifically, it focuses on the development of a low-cost CNC machine, named ‘Gorosito’, which includes various customisation elements, such as the ability to interchange drawing tools to suit the operator/artist. Experimental validation of Gorosito is performed using images generated with generative AI and also including a comparison of the results with those produced by a commercial CNC machine. Results reveal precision of 0.045 mm and a 34% cost saving comparing with other commercial solutions. Our findings also show that each artwork, derived from the same digital file, acquires a unique expression, which leads to a redefinition of authenticity in digital art and provides a renewed perspective on the interplay between technology, artistic creation and cultural perception. The study thus positions Gorosito as an open and reproducible framework that any creative-code laboratory can adopt, bridging machine learning research with low-cost digital fabrication.